OPTIMALISASI DIGITAL MARKETING DAN BRANDING PADA UKM OMAH W+ CATERING DI KEC. SIDOREJO KOTA SALATIGA - Maharani, Luky Nugraha Putri; Meirawati, Eka; Amira, Diyah Ayu Fara; Asna, Wahyu Husnul; Arifudin, Dirga; Fatma, Kurnia Aulidia; Hidayah, Nurul Arifatul; Aminah, Siti; Qurniawati, Rina Sari; Wulandari, Ernia Diyah Ayu (Sekolah Tinggi Ilmu Ekonomi AMA, 2025)
The rapid development of digital technology since the advent of the internet has brought many changes in various fields, including the business world. The technology allows anyone to connect easily and quickly to the entire world. Small and Medium Enterprises (SMEs) can now utilize digital technology to help make better decisions, improve business activities, and reach customers more widely and effectively. An example of digital implementation can be seen in the Omah W+ Catering Salatiga SMEs, which operates in the culinary sector and faces challenges in business strategy and promotion. Through the Community Empowerment Practice Lecture (CEPL), students play a role in assisting and developing these SMEs by providing education, solutions, and assistance in using social media for marketing. One concrete step taken was the creation of social media accounts for online product marketing. This strategy provides information about the Omah W+ Catering Salatiga SMEs through these accounts.